2018
DOI: 10.1128/jvi.01302-17
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus: Targeting the G Protein Provides a New Approach for an Old Problem

Abstract: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infection (LRTI) annually affecting >2 million children in the United States <5 years old. In the elderly (>65 years old), RSV results in ∼175,000 hospitalizations annually in the United States with a worldwide incidence of ∼34 million. There is no approved RSV vaccine, and treatments are limited. Recently, a phase 3 trial in the elderly using a recombinant RSV F protein vaccine failed to meet its efficacy objectives, namely, prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 52 publications
1
63
0
1
Order By: Relevance
“…Symptomatic supportive care and Palivizumab are currently available options to RSV disease clinical management, which reduce the symptoms and severity, decreasing hospitalization rate but not mortality [15][16][17][18]. Fortunately, RSV vaccines are progressing in phase III clinical trials and could be available in the coming years [19], being G protein suggested as a plausible target [20]. Therefore, ongoing global surveillance and characterization of circulating RSV strains are required for evidence-based vaccination policies.…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic supportive care and Palivizumab are currently available options to RSV disease clinical management, which reduce the symptoms and severity, decreasing hospitalization rate but not mortality [15][16][17][18]. Fortunately, RSV vaccines are progressing in phase III clinical trials and could be available in the coming years [19], being G protein suggested as a plausible target [20]. Therefore, ongoing global surveillance and characterization of circulating RSV strains are required for evidence-based vaccination policies.…”
Section: Introductionmentioning
confidence: 99%
“…Because these vaccines contained RSV F immunogen in its post-fusion conformation, one emerging approach is focused on the generation of RSV F immunogens that are stabilized in the pre-fusion conformation, as revealed by X-ray crystallographic studies (8). Additionally, RSV G is increasingly recognized as a critical target (9), yet its development as a vaccine antigen has been hindered by its dense and heterogeneous N- and O-glycosylation in the highly-variable mucin-like regions and a paucity of information correlating specific molecular structure with biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, anti-G antibodies are associated with lower clinical disease severity scores, despite an abundance in sera more than 30 times lower than anti-F antibodies (8). Thus, the RSV G protein is increasingly recognized as an important target for RSV vaccine and therapeutic antibody development (22). RSV G is a type II membrane protein containing two mucin-like regions coated with 30 to 40 O-linked glycans and 3 to 5 N-linked glycans ( Fig.…”
mentioning
confidence: 99%